Chinese Consumers’ Ethical Beliefs: An Investigation Into Chinese Consumers’ Attitudes Towards Businesses Affecting Their Ethical Beliefs - YUAN, RUIZHI (2011)
In the past decade, there has been an increased awareness of consumer unethical behaviour in Asian countries, because Asian consumers are supposed to be more engaged in the production of counterfeit products and using computer software without paying than Western consumers (Chan et al., 1998). How do they judge the ethically questionable behaviours? What factors affecting their ethical beliefs? These questions are important for companies wishing to reduce consumer unethical behaviours. They are also important to the government who want to improve business environment and ensure ethical trade and also protect intellectual property rights. For modern enterprises, it is extremely critical to investigate whether consumers’ attitudes towards businesses influence their ethical beliefs. This study explores the linear logic between consumers’ attitudes towards businesses and consumer ethical beliefs in a Chinese context. The present study uses a consumer ethics scale introduced by Muncy & Vitell (1992) to determine consumers’ ethical beliefs through 116 valid questionnaires. The factor analysis results show that the dimensions of consumer ethics scale for Chinese consumers are somewhat similar compared with western consumers. Among four dimensions of consumer ethics scale, Chinese consumers are more acceptable to ‘actively benefiting from questionable actions’ while perceive ‘actively benefiting from illegal activities’ as most unacceptable. Moreover, consumers’ attitudes towards businesses do have significant positive relationships with both ‘passively benefiting at the expense of others’ and ‘no harm/no foul’ ethical dimensions. Thus, it is imperative for Chinese companies and government to promote consumer education and develop better customer-business relationship in order to change consumers’ ethical beliefs, leading to and hence reducing unethical consumer behaviour.